(untitled) (Kriminalističke teme, 2007)
Protagoras once said, theorem: man is the measure of all things, those which are and which are not. Guidance to this work is actually that thought. Value of that Philosophical theorem cannot be measured metrically, like time is measured by clock. It stays without time duration, or better it goes beyond time and space. Every profession today is represented and brings responsibility: scientific, technical, political etc. Today, especially, inevitability of the need of potential of science, political and moral norm and its unity is essential. This article analyses state of moral responsibility in global world.